1999
DOI: 10.1074/jbc.274.13.8770
|View full text |Cite
|
Sign up to set email alerts
|

The α-Helical Domain of Gαt Determines Specific Interaction with Regulator of G Protein Signaling 9

Abstract: RGS proteins (regulators of G protein signaling) are potent accelerators of the intrinsic GTPase activity of G protein ␣ subunits (GAPs), thus controlling the response kinetics of a variety of cell signaling processes. Most RGS domains that have been studied have relatively little GTPase activating specificity especially for G proteins within the G i subfamily. Retinal RGS9 is unique in its ability to act synergistically with a downstream effector cGMP phosphodiesterase to stimulate the GTPase activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 55 publications
3
56
1
Order By: Relevance
“…For example, it was shown by crystal structure analysis that the G o LOCO motif (also called G protein regulatory motif), which is found in some GTPase-activating proteins of the RGS (regulator of G protein signaling) family (e.g. RGS12 and RGS14), binds to the all-helical domain of G proteins (22,23). Also AGS proteins (activators of G protein signaling), which function as guanine nucleotide dissociation inhibitors, possess a G o LOCO domain (24).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was shown by crystal structure analysis that the G o LOCO motif (also called G protein regulatory motif), which is found in some GTPase-activating proteins of the RGS (regulator of G protein signaling) family (e.g. RGS12 and RGS14), binds to the all-helical domain of G proteins (22,23). Also AGS proteins (activators of G protein signaling), which function as guanine nucleotide dissociation inhibitors, possess a G o LOCO domain (24).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results have revealed PDE␥ stimulation of GAP activity of RGS9 (11,26,27), and inhibition of RGS4, RGS16, and GAIP (12)(13)(14). In addition, we analyzed RGS6 and RGS11, and found that RGS6 was inhibited and RGS11 was unaffected when the RGS domain of each was expressed as a GST fusion, and assayed with or without PDE␥ (Fig.…”
Section: A Cluster Of Rgs Residues May Mediate Rgs-effector Interactimentioning
confidence: 99%
“…LY has been used successfully in several studies to report protein conformational changes (22) or protein association (23). LY-labeled SRII-S154C was divided into several different aliquots with equal volumes and different concentrations of HtrII (Fig.…”
Section: Tryptophans Placed Within a Short Region In The Htrii Membramentioning
confidence: 99%